Effect of self-treatment process on properties of natural fiber-reinforced geopolymer composites - Phattharachai Maichin (2020)
© 2020, © 2020 Taylor & Francis. Natural (hemp) fibers can be used in the cementitious composite as they have superb engineering properties, e.g. environmentally friendly and offer economic advantages. However, alkaline treatment (alkalization) process of natural fiber prior to mixing is required to modify fiber surface, making fibers more adhesive and compatible with cement paste. Geopolymer, one of the green alternative cementitious materials, is fortuitously involved in the alkaline environment, as alkaline solutions are used as its activators. The latent benefit, regarding the influence of alkalinity in geopolymer systems, namely ‘self-treatment process’ was thus investigated. The self-treatment process is a ‘Just-adding’ of as-received hemp fibers into geopolymer mixture without any pre-alkaline treatments. The results showed that the self-treatment process was governed by the alkaline environment in the geopolymer system and alternatively acted as an alkaline treatment condition for natural fibers, indicated by SEM and FT-IR analysis. The pre-alkalization process can be skipped in the self-treatment approach with similar mechanical properties to the ordinary processes. The main findings of this work could be further tailored to partially or fully the conventional alkaline treatment process and provide an opportunity for any other natural fiber geopolymer composites to be easily utilized in massive amount and used in practical applications.